Another story about the miracle of Jinadatta Suri - Temples of India Project Team (Jio Institute, 2024)
The fourteenth oval painting (in clockwise order) in the lower/outer circle in the ceiling of the mandapa (pillared hall) is another story about the miracle of Jinadatta Suri. Once, somewhere in Gujarat, with the evil intent of troubling the Jains, some people placed a cow in front of the Jain Temple. Jinadatta Suri, using his powers, placed the cow in front of the Shiva Temple. Interestingly, the Hindu temple, with a Shiva linga inside, is shown with a domical spire, while the Jain Temple is shown with a Tirthankara enshrined in it, featuring a multi-spired roof. The painting includes two cows, one sitting in front of the Jain Temple, and the other standing in front of Jinadatta Suri. Jinadatta presumably also restored life to the cows. A disciple accompanies him. The inscription reads, ‘Shri Jinadatta Suri ji Gavu ji la hi.’